Efektivitas Dan Evaluasi Pembelajaran Inklusi Di SMP 11 Kota Tangerang Selatan - Fadilatul Jannah; Siti Khoeriyah; Ika Ika (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Children with special needs have become the concern of various parties, especially in Indonesia. Students with special needs have the right to receive the same education as other students based on Constitution No. 20 of 2003 concerning the National Education System which states that the state provides full guarantees for children with special needs to obtain quality educational services. Education is a conscious, planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state.